Corruption Chronicles A Mock Trial Approach in KIAR to Corporate Liability - Hadijah, Ahmad (UMPSA, 2024)
Approximately 1,400 students took KIAR course in Semester I 2023/2024, ranging from Bachelor’s degree students to Diploma students. Each had to undergo a mock trial assessment as part of their assessment of corruption and abuse of power in the workplace and daily activities. Professionals from the Malaysian Anti-Corruption Commission (MACC) and Integrity and Compliance Unit, UMPSA, evaluted the students’ depth of understanding of Section 17A liability corporations during the two-week assessment period.